Crystallization kinetics of polymer fibrous nanocomposites. (October 2016) - Galeski, Stanislaw; Piorkowska, Ewa; Rozanski, Artur; Regnier, Gilles; Galeski, Andrzej; Jurczuk, Kinga
Graphical Abstract: Highlights: A model was developed describing the overall crystallization kinetics in the nanofiber reinforced polymer nanocomposites. The model was verified by computer simulation. The overall crystallization kinetics depended on the nanofiber content, nucleation ability and length. The overall crystallization kinetics did not depend on the nanofiber orientation and shape. The theoretical prediction agreed with experimental results. Abstract: Through applying both a probabilistic approach and a combination of probabilistic and the Avrami 'extended volume' approaches we have derived a theory of overall crystallization kinetics of polymers reinforced with nanofibers. The theory describes the crystallization kinetics in the presence of straight or curved nanofibers, with different nucleation ability and orientation, and allows to account for their variable length. The analytic results are supported by computer simulations of spherulitic structures. The derived mathematical formulas are in exponential forms suggesting the use of the Avrami logarithmic coordinates for detailed analysis of experimental data. Experimental data on crystallization of several nanocomposites, including polypropylene reinforced with poly(tetrafluoroethylene) nanofibers and polyamide 12 with carbon nanotubes, are in a good agreement with the theoretical predictions.